2014
DOI: 10.4314/ejhs.v24i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functionality and Self-Rated Health Status of Adult Patients with Knee Osteoarthritis Presenting in a Primary Care Clinic

Abstract: BACKGROUND: Knee osteoarthritis is a chronic medical condition of public health importance in Nigeria which causes disability and impacts daily activities in the sufferers. This study aimed to describe the physical functionality and self-rated health status of adult patients with clinical knee osteoarthritis presenting at the Family Medicine Department, University College Hospital, Ibadan, Nigeria. METHODS: This was a cross-sectional study of 400 respondents. Knee osteoarthritis was diagnosed clinically using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…The WHR is considered a routine measure for health education and decreases the impact of knee OA on public health (OGUNBODE et al, 2014). All volunteers in the research presented a ratio higher than 0.81, and 37% of the total population presented a ratio higher than 0.9, which according to the WHO (1995) represents a greater chance of developing cardiovascular complications.…”
Section: Discussionmentioning
confidence: 88%
“…The WHR is considered a routine measure for health education and decreases the impact of knee OA on public health (OGUNBODE et al, 2014). All volunteers in the research presented a ratio higher than 0.81, and 37% of the total population presented a ratio higher than 0.9, which according to the WHO (1995) represents a greater chance of developing cardiovascular complications.…”
Section: Discussionmentioning
confidence: 88%
“…The literature search yielded no studies citing the use of this parameter in relation to specific disease entities. We employed the described methods in clinical practice because OAK patients develop a number of undesirable anatomical changes that negatively affect the knee joint position sense [27,40,41] and cause pain [21,26] and functional deficits [2,3,7,12,30]. Therefore, based on available data from other studies [27,42], we determined that the treatment algorithm for OAK patients should include therapeutic procedures that improve joint position sense and overall function while reducing pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis of the knee (OAK), even with unilateral presentation of symptoms, causes a significant deterioration of function, which, in turn, lowers patients' quality of life. In broader terms, it poses a significant public health problem [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This is noteworthy because a more recent finding by Ogunbode et al reported that majority of respondents with knee osteoarthritis reported that the presence of the disease affected their self-rated health adversely. 6 A study on perceived family support of patients with type II diabetes mellitus in University College Hospital, Ibadan in 2007 revealed an inverse relationship between levels of perceived family support and blood glucose control. 19 Furthermore, there was also a statistically significant association between strong support from friends and good health perception in our study.…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…5 Ogunbode et al in 2014 reported that knee osteoarthritis significantly impaired the health and daily activities of adult patients in Ibadan, Nigeria. 6 Guidelines published by the American College of Rheumatology Diagnostic and Therapeutic Criteria Committee provide the classification of osteoarthritis as a clinical syndrome in older adults who present with joint pain, tenderness, limitation of movement, early morning stiffness and joint crepitus. 8 In clinical practice the diagnosis of knee osteoarthritis is often made on the basis of history and physical examination.…”
Section: Introductionmentioning
confidence: 99%